Acquired Immunoglobulin G deficiency in stroke patients and experimental brain ischemia - Liesz, Arthur; Roth, Stefan; Zorn, Markus; Sun, Li; Hofmann, Kerstin; Veltkamp, Roland (Experimental neurology, 2015)
Acute brain injuries induce a systemic immune depression syndrome (SIDS) that predisposes patients to bacterial infections. While cellular compartments of this syndrome have been well characterized, the contribution of humoral immune mechanisms and particularly immunoglobulins to SIDS has not been investigated so far.
Gesehen am 23.06.2020